1996
DOI: 10.1016/0014-5793(96)00783-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of annexin V in the entry of influenza viruses and role of phospholipids in infection

Abstract: capsid protein of FPV and that against annexin 33 kDa were obtained from Drs Becht and Lim as previously described [2]. Anti-annexin V Abstract Influenza viruses bind to annexin V, a widely spread antiserum was produced in a rabbit by immunizing with 50 ~g of non-glycosylated phospholipid-binding protein. Externally added annexin V in the presence of Freund's adjuvant at monthly intervals phospholipids as well as antiserum against this protein specifiover a period of 2 months. The highest antibody titer obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 21 publications
1
24
1
Order By: Relevance
“…These results differ from a previous study, which suggested that A5 could serve as a second receptor for viral entry (48). The precise physiological role of A5 remains to be determined.…”
Section: Discussioncontrasting
confidence: 99%
“…These results differ from a previous study, which suggested that A5 could serve as a second receptor for viral entry (48). The precise physiological role of A5 remains to be determined.…”
Section: Discussioncontrasting
confidence: 99%
“…Anionic phospholipids, including PS, have been implicated as receptors and cofactors for several viruses, including VSV, rhabdoviruses, hepatitis B, influenza viruses, hemorrhagic septicemia, Sendai virus, rubella virus, and Sindbus virus (33)(34)(35)(36)(37)(38)(39)(40). Characterization of lipid composition of HIV-1 envelope shows that many lipids, including glycosphingolipids, cholesterol, and PS, are found in the membrane at a higher frequency than what is represented in the host membrane, suggesting a selective incorporation of these lipids (14).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was reported that Annexin V aids in the entry of influenza virus and that annexins may serve as a receptor for the viruses (Huang et al, 1996). However, different annexins have different impact on influenza virus replication.…”
Section: A) Annexins and Influenza Infectionmentioning
confidence: 99%